(untitled) (American Journal of Islam and Society, 1992)
This is a collection of anthropological studies on the dynamics of the implementation oflaw in the Middle East. The basic arguments of the book raise the issue of the context of law and the role of Islamic law in the Middle East. The editor, Daisy Dwyer, contends that context rather than the letter of the law is the core phenomenon determining the handling and outcome of legal cases. The form and impact of Islamic law varies according to the specific regional and cultural context . Dwyer also argues that Islamic law is often invoked not so much for its specific content but as a political symbol relating the past to the present and, ultimately, the future. These points are significant for understanding the impact of Islamic law in the Middle East. The cultural context will consistently influence which proBook visions of the law are emphasized and which provisions are deemphasized or conveniently forgotten. Furthermore, social outlooks and cultural habits will in turn impact upon huw the specific provisions are interpreted and implemented. As Safia Mohsen demonstmtes in an insightful article on mmen and the criminal justice system in Egypt, the implementation of law responds to the specific situation of women in Egypt. The way criminal law is implemented sometimes discriminates, depending on the context, in favor of or against women ...